Three Acupoints of Acupressure Improve the Anxiety Level in Cancer Patients based on Types of Cancer Therapy - Yesiana Dwi Wahyu Werdani (Indonesian Journal of Cancer, 2019)
Background: Cancer and its therapeutic management trigger the multiorgans physical disorders, that can cause the patient to worry and become anxious about the condition. Three acupoints of acupressure therapy stimulates relaxation of the body and can reduce anxiety. The purpose was to determine the influence of three acupoints of acupressure therapy to improve the anxiety level in cancer patients based on types of cancer therapy.Methods: This was an interventional study using pre-experiment pre-test post-test design. Samples were 30 cancer patients living at the Indonesian Cancer Foundation East Java Branch Surabaya Indonesia, taken by purposive technique sampling based on inclusion criteria. The instrument was Beck Anxiety Inventory that it was valid and reliable based on the test. Ethical feasibility tests has been carried out. Acupressure therapy is given on acupoint St36, Li4 and Li11. It conducted 2 times per week for 4 weeks. Wilcoxon Signed Rank Test was applied to analyze this result with p < 0.05.Results: There was a significant effect of acupressure for improving anxiety levels in both groups with p value in the chemotherapy group 0.001 and in the chemoradiotherapy group 0.002. But a greater influence occurred in the chemotherapy group compared to chemoradiotherapy group.Conclusions: Acupressure therapy in three acupoints can stimulate relaxation condition, it can decrease the anxiety level for cancer patients with all types of cancer therapy.